Modified “Allele-Specific qPCR” Method for SNP Genotyping Based on FRET - Kalendar, Ruslan; Baidyussen, Akmaral; Serikbay, Dauren; Zotova, Lyudmila; Khassanova, Gulmira; Kuzbakova, Marzhan; Jatayev, Satyvaldy; Hu, Yin-Gang; Schramm, Carly; Anderson, Peter A.; Jenkins, Colin L. D.; Soole, Kathleen L.; et al. (Frontiers in Plant Science, 2022)
The proposed method of improved and universal ‘Allele-specific q-PCR’ (ASQ) for genotyping of Single nucleotide polymorphism (SNP) is based on Fluorescence resonance energy transfer (FRET). This method is similar to frequently used techniques like Amplifluor, Amplifluor-like and KASP, as well as others employing common Universal probes (UPs) for SNP analyses. The advantage of the proposed ASQ method is that the fluorophores and quenchers do not combine together in a ‘hair-pin’ loop-structure but, instead, are inserted separately to complementary oligonucleotides. The UPs with fluorescent dyes and quenchers have different annealing temperatures due to their oligonucleotide lengths of 19-bp and 13-bp, respectively. Fluorophores can effectively bind amplified allele-specific PCR products at higher sub-optimal annealing temperature (62°C). The subsequent extension temperature must then be decreased (55°C), which allows the common quencher in excess concentration to bind and quench all non-incorporated UPs with dyes. The SNP site is positioned at a penultimate base in each allele-specific primer, which increases the reaction specificity and allele discrimination. The proposed ASQ method is advanced in providing very clear and effective measurement of the fluorescence emitted, with very low signal background-noise, and simple procedures convenient for customised modifications and adjustments. Importantly, this ASQ method is two- to ten-fold cheaper than Amplifluor and KASP, respectively, and much cheaper than all those methods that rely on dual-labelled probes without Universal components, like TaqMan and Molecular Beacons. Results for SNP genotyping in the barley gene HvSAP16, controlling stress-associated proteins, are presented as proven example. Moreover, this method is very suitable not only for bi-allelic uniplex reactions but also for 3- or 4-allelic variants or different SNPs in a multiplex format in a range of applications including medical, forensic or others involving SNP genotyping.